Lipoprotein(a): Pathophysiology, measurement, indication and treatment in cardiovascular disease. A consensus statement from the Nouvelle Société Francophone d’Athérosclérose (NSFA) - Durlach, Vincent; Bonnefont-Rousselot, Dominique; Boccara, Franck; Varret, Mathilde; Di-Filippo Charcosset, Mathilde; Cariou, Bertrand; Valero, René; Charriere, Sybil; Farnier, Michel; Morange, Pierre E.; Meilhac, Olivier; Lambert, Gilles; et al. (Archives of cardiovascular diseases, 2021)
Central Illustration. Pathophysiological pathways providing a causal link between high plasma concentrations of lipoprotein(a) (Lp(a)) and atherosclerotic vascular disease and aortic valve stenosis (AVS). Clinical outcomes are related to accelerated atherosclerosis complicated by atherothrombosis (myocardial infarction, stroke), peripheral artery disease (PAD) or aortic valve replacement (AVR) caused by valve calcification and aortic stenosis. Apo(a): apolipoprotein(a); LDL: low-density lipoprotein; OxPL: oxidized phospholipids; NSFA: Nouvelle Société Francophone d’Athérosclérose; SP: serine-protease domain; V: plasminogen kringle V (reproduced with permission).▪ •Lp(a) plays a causal role in CVD and AVS.•Lp(a) is an apo B100-containing LDL-like particle associated with apo(a).•The partial homology of apo(a) with plasminogen results in hypofibrinolysis.•The best CVD risk predictor is circulating Lp(a) concentration.•Lp(a) must be measured once in subjects at high cardiovascular risk. Lipoprotein(a) is an apolipoprotein B100-containing low-density lipoprotein-like particle that is rich in cholesterol, and is associated with a second major protein, apolipoprotein(a). Apolipoprotein(a) possesses structural similarity to plasminogen but lacks fibrinolytic activity. As a consequence of its composite structure, lipoprotein(a) may: (1) elicit a prothrombotic/antifibrinolytic action favouring clot stability; and (2) enhance atherosclerosis progression via its propensity for retention in the arterial intima, with deposition of its cholesterol load at sites of plaque formation. Equally, lipoprotein(a) may induce inflammation and calcification in the aortic leaflet valve interstitium, leading to calcific aortic valve stenosis. Experimental, epidemiological and genetic evidence support the contention that elevated concentrations of lipoprotein(a) are causally related to atherothrombotic risk and equally to calcific aortic valve stenosis. The plasma concentration of lipoprotein(a) is principally determined by genetic factors, is not influenced by dietary habits, remains essentially constant over the lifetime of a given individual and is the most powerful variable for prediction of lipoprotein(a)-associated cardiovascular risk. However, major interindividual variations (up to 1000-fold) are characteristic of lipoprotein(a) concentrations. In this context, lipoprotein(a) assays, although currently insufficiently standardized, are of considerable interest, not only in stratifying cardiovascular risk, but equally in the clinical follow-up of patients treated with novel lipid-lowering therapies targeted at lipoprotein(a) (e.g. antiapolipoprotein(a) antisense oligonucleotides and small interfering ribonucleic acids) that markedly reduce circulating lipoprotein(a) concentrations. We recommend that lipoprotein(a) be measured once in subjects at high cardiovascular risk with premature coronary heart disease, in familial hypercholesterolaemia, in those with a family history of coronary heart disease and in those with recurrent coronary heart disease despite lipid-lowering treatment. Because of its clinical relevance, the cost of lipoprotein(a) testing should be covered by social security and health authorities. La lipoprotéine(a) est une lipoprotéine de basse densité riche en cholestérol, contenant de l’apolipoprotéine B100, associée à une deuxième protéine majeure, l’apolipoprotéine(a). L’apolipoprotéine(a) présente une similitude structurelle avec le plasminogène mais n’a pas d’activité fibrinolytique. En raison de sa structure composite, la lipoprotéine(a) peut : (1) exercer une action prothrombotique/antifibrinolytique favorisant la stabilité du caillot ; et (2) favoriser la progression de l’athérosclérose par sa propension à la rétention dans l’intima artérielle avec dépôt de sa charge en cholestérol aux sites de formation de la plaque. De même, la lipoprotéine(a) peut induire une inflammation et une calcification dans l’interstitium de la valve du feuillet aortique, entraînant une sténose calcifiante de la valve aortique. Des preuves expérimentales, épidémiologiques et génétiques soutiennent l’affirmation selon laquelle des niveaux élevés de lipoprotéine(a) sont liés de manière causale au risque athérothrombotique et également à la sténose calcifiante de la valve aortique. La concentration plasmatique de lipoprotéine(a) est principalement déterminée par des facteurs génétiques, n’est pas influencée par les habitudes alimentaires, reste essentiellement constante tout au long de la vie pour un individu donné et constitue le paramètre le plus puissant pour prédire le risque cardiovasculaire associé à la lipoprotéine(a). Cependant, des variations interindividuelles majeures (jusqu’à 1000 fois) sont caractéristiques des niveaux de lipoprotéine(a). Dans ce contexte, les dosages de la lipoprotéine(a), bien qu’actuellement insuffisamment standardisés, présentent un intérêt considérable non seulement pour la stratification du risque cardiovasculaire, mais également pour le suivi clinique des patients traités par de nouvelles thérapies hypolipémiantes ciblées sur la lipoprotéine(a) (par exemple les oligonucléotides antisens anti-apolipoprotéine(a) et les petits acides ribonucléiques interférents) qui réduisent sensiblement les concentrations circulantes de la lipoprotéine(a). Nous recommandons que la lipoprotéine(a) soit mesurée une fois chez les sujets à haut risque cardiovasculaire présentant une maladie coronarienne prématurée, dans l’hypercholestérolémie familiale, chez ceux ayant des antécédents familiaux de maladie coronarienne et chez ceux présentant une maladie coronarienne récurrente malgré un traitement hypolipidémiant. En raison de sa pertinence clinique, le coût du test lipoprotéine(a) devrait être couvert par la sécurité sociale et les autorités sanitaires.